Transient dynamic analysis of shear deformable shallow shells using the boundary element method. (15th March 2015) - Useche, J.; Albuquerque, E.L.
Highlights: Dynamic analysis of shallow shells using a boundary element formulation. Boundary element formulation based on a direct time-domain formulation. Shear deformation and rotatory inertia were included in the formulation. Reissner's plate theory and plane stress elasticity are used. Integrals related to inertial terms are treated using DRBEM. Abstract: Dynamic plate bending problems appear on civil, mechanical, aerospatial and naval applications. The complexity involved in the dynamic response of plates brings many challenges from a mathematical standpoint. In this work, the transient dynamic analysis of elastic shallow shells under uniformly distributed pressure loads, using a dual reciprocity boundary element formulation, is presented. A boundary element formulation based on a direct time-domain formulation using elastostatic fundamental solutions was used. Effects of shear deformation and rotatory inertia were included in the formulation. Shallow shells are modeled coupling boundary element formulation of shear deformable plate and two-dimensional plane stress elasticity. Domain integrals related to inertial terms were treated using the Dual Reciprocity Boundary Element Method. Numerical examples are presented to demonstrate the efficiency and accuracy of the proposed formulation.